2021
DOI: 10.1108/ijebr-09-2020-0602
|View full text |Cite
|
Sign up to set email alerts
|

Confronting the unprecedented: micro and small businesses in the age of COVID-19

Abstract: PurposeThe purpose of this study is to understand how micro and small firms are navigating through the coronavirus disease 2019 (COVID-19) threat, and the alternatives they are implementing to coexist with the ongoing crisis. To this end, Italy's socioeconomically and traditionally significant wine industry is examined. The study considers insights of the theory of planned behaviour (TPB) and develops a theoretical framework, which proposes various emerging theoretical dimensions, including proactiveness, supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 47 publications
7
38
1
4
Order By: Relevance
“…Finally, even if the data were collected before the health crisis caused by the COVID-19 pandemic, the implications of this study become even more relevant in this critical scenario. The pandemic can be considered a structural shock that changed the dynamics of global trade and production, which seriously affected SMEs already experiencing difficulties (Bressan et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, even if the data were collected before the health crisis caused by the COVID-19 pandemic, the implications of this study become even more relevant in this critical scenario. The pandemic can be considered a structural shock that changed the dynamics of global trade and production, which seriously affected SMEs already experiencing difficulties (Bressan et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding job performance, self-reported job performance measurement instruments are adequate and provide a better measure than official evaluation scores from immediate supervisors (Bressan, Duarte Alonso, & Kok, 2021). To paraphrase, anonymous self-evaluations of job performance are a better instrument of quality perspective than official annual performance reviews produced by supervisors.…”
Section: Job Performancementioning
confidence: 99%
“…The COVID-19 pandemic has seen socio-economic turmoil on an unprecedented global scale (Bressan et al, 2021), and in many countries micro and small businesses have been affected most by lockdown measures (Cucculelli and Peruzzi, 2020); the performing arts are amongst those businesses worst affected. Early research studies indicated two basic business responses: exit from the industry, or innovation.…”
Section: Context and Theoretical Framingmentioning
confidence: 99%
“…Other authors underlined the significance of mindsets towards the crisis (e.g. resourcefulness and proactiveness), subjective norms, perceived behavioural control, firm owners-managers’ entrepreneurial self-efficacy, controllability and coping capabilities (for Italian wine producers; Bressan et al, 2021).…”
Section: Context and Theoretical Framingmentioning
confidence: 99%